2010
DOI: 10.1073/pnas.1008365107
|View full text |Cite
|
Sign up to set email alerts
|

Multiple oncogenic mutations and clonal relationship in spatially distinct benign human epidermal tumors

Abstract: Malignant tumors result from the accumulation of genetic alterations in oncogenes and tumor suppressor genes. Much less is known about the genetic changes in benign tumors. Seborrheic keratoses (SK) are very frequent benign human epidermal tumors without malignant potential. We performed a comprehensive mutational screen of genes in the FGFR3-RAS-MAPK and phosphoinositide 3-kinase (PI3K)-AKT pathways from 175 SK, including multiple lesions from each patient. SK commonly harbored multiple bona fide oncogenic mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
86
1
6

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 86 publications
(100 citation statements)
references
References 59 publications
(56 reference statements)
7
86
1
6
Order By: Relevance
“…Patients with germline mutations in FGFR3 that result in the same codon change as in somatic mutations found in SK do not develop malignant epithelial skin tumors at increased frequency (2). The authors show that the sites of mutations found at the highest frequency in SK are found at much lower frequency in malignant tumors and vice versa (1). Although a subset of the mutations found in SK exhibits lower transforming activity than those found more frequently in malignant tumors, many of these mutations do predispose to tumor development in animal models.…”
Section: Discussionmentioning
confidence: 77%
See 4 more Smart Citations
“…Patients with germline mutations in FGFR3 that result in the same codon change as in somatic mutations found in SK do not develop malignant epithelial skin tumors at increased frequency (2). The authors show that the sites of mutations found at the highest frequency in SK are found at much lower frequency in malignant tumors and vice versa (1). Although a subset of the mutations found in SK exhibits lower transforming activity than those found more frequently in malignant tumors, many of these mutations do predispose to tumor development in animal models.…”
Section: Discussionmentioning
confidence: 77%
“…Nonmalignant or low-grade urothelial tumors that derive from an epithelial structure related to skin may inform the findings of Hafner et al (1). These tumors frequently harbor the same FGFR3 mutations, tend to be genomically stable, and arise in a mulifocal manner (14).…”
Section: Commentarymentioning
confidence: 75%
See 3 more Smart Citations